HERO’S JOURNEY SHIFT OF HERCULES FROM MOORE’S HERCULES: THE THRACIAN WARS TO ITS MOVIE ADAPTATION - Himawan Tusprianto (CrossOver, 2021)
This study was aimed to reveal the shift of hero’s journey archetypes in presenting Moore’s Hercules comic book to its movie adaptation. Therefore, the researcher dealt with the comic book and the movie adaptation as the object of the study, in which adaptation and archetypes frames are applied as the theories to analyze the data. The result of the study was the explanation upon the shifts appeared in the adapted work and the reasons behind the shifts. This research belonged to the qualitative research field. To collect the data, the researcher used the documentation technique. Then the collected data were arranged based on its classification. The technique of analyzing the data was content analysis. It was meant to draw the pattern of archetypes that is seen within the content both in comic book and its movie adaptation. Furthermore, making shifts in the product of adaptation in regard to the audiences was considered as the pattern, too. Based on the analysis, it was found that the movie adaptation was unfaithful adaptation towards Moore’s. The comic book version delivered the story in sadistic and bloody tone which could be seen from the pictorial images in the panels or words within the balloon text. It was such a contradiction with what were presented in the movie version. The researcher found that the comic book version brought Hercules in a “rampant mode”, while the movie version presented him in a “savior mode”. There were two reasons why the adapter made these shifts. It was because of the values that were believed by the target audiences and because the movie production had to deal with the law, culture, and movie industry movement. Thus, inappropriate things had to be replaced or transformed to be more acceptable for the wider societies.